Practical spiritualities in a media age - Coats, Curtis (Bloomsbury Academic, 2015)
1. Introduction: The Webs We Spin: Relational, Mediated, Spiritual / By Curtis Coats, Ph.D., (Millsaps College) and Monica Emerich, Ph.D. (Groundwork Research and Communications; University of Colorado) -- 2. Mediated Babywearing as Aesthetic Orthodoxy / By Florence I. Pasche Guignard, Ph.D. (University of Toronto) -- 3. Spirituality at Work: Servant Leadership in the Western Workplace / By RuthAnn Ritter and Jeffrey Mahan, Ph.D. (Iliff School of Theology) -- 4. "Helping Glastonbury To Come into its Own": Practical Spirituality, Materiality, and Community Cohesion in Glastonbury / By Marion Bowman, Ph.D. (The Open University) -- 5. Hula Hoop Spiritualities: Social Media, Embodied Experience, and Communities of Practice / By Jenna Gray-Hildenbrand, Ph.D. (Middle Tennessee State University) and Martha Smith Roberts (University of California, Santa Barbara) -- 6. "Another Way": Modernist Artists, Media, and the Desire for Spiritual Community / By Jeremy Garber, Ph.D. (Iliff School of Theology) -- 7. "Dancing Our Prayers": Material Culture and Practical Spiritualities of the Jam Band Scene / By Lucas F. Johnston, Ph.D. (Wake Forest University, Department of Religion and Center for Energy, Environment and Sustainability) -- 8. The Spirit of Place: Identity and Media in Relation to Cornwall / By Garry Tregidga, Ph.D. (Institute of Cornish Studies, University of Exeter) -- 9. Spiritual Narratives and The Icarus Project: Disidentification and Rhetoric of Liberation / By Liz Barr (University of Wisconsin) -- 10. Strategic Confession: Pragmatic Religion and Spirituality in the PostSecret Community / By Rachel Liberman, Ph.D. (University of Denver) and Stewart M. Hoover, Ph.D. (University of Colorado) -- 11. A Constructed Category: Baby Boomers Navigating Aging through Spirituality and the Media / By Anne Maija Huffman, Ph.D. (Sofia University) -- 12. Food, Sex, and Spirituality / By Graham Harvey, Ph.D. (The Open University) -- Bibliography -- Index.